2018
DOI: 10.9734/ajocs/2018/44094
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Abattoir Wastes on Soil Microbial and Physicochemical Properties

Abstract: Influence of abattoir wastes on physicochemical and microbiological properties of soil samples obtained from Akwa Ibom State, Southern Nigeria were investigated using standard analytical and microbiological methods. Studied abattoirs and the control soils were in the sandy-clay-loamy soil category with varying quantities of sand, silt and clay. Bulk density, pH, electrical conductivities, salinity, moisture content, total organic and carbon content, cation exchange capacities, total petroleum hydrocarbon, nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…According to [2] soil organic matter usually acts as a store house or reservoir for most metals hence can influence their bioavailability in the soil. Results of Table 2 show that at soil depths 0 -20 cm and 20 -40 cm, the mean organic matter contents of the soil samples were, 8.34 ± 0.34 and 6.41% ± 0.51% for auto-mechanic workshops; 2.20 ± 0.14 and 1.53% ± 0.10% for fuel filling stations;…”
Section: Organic Matter (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…According to [2] soil organic matter usually acts as a store house or reservoir for most metals hence can influence their bioavailability in the soil. Results of Table 2 show that at soil depths 0 -20 cm and 20 -40 cm, the mean organic matter contents of the soil samples were, 8.34 ± 0.34 and 6.41% ± 0.51% for auto-mechanic workshops; 2.20 ± 0.14 and 1.53% ± 0.10% for fuel filling stations;…”
Section: Organic Matter (%)mentioning
confidence: 99%
“…Human activities in urban areas largely contribute to the contamination of urban soils and this is a major environmental concern. Studies have shown that environmental pollution and its attendant problems on land, air and water qualities are severe now than ever [2]. There are several evidences to this fact, ranging from soil fertility loss, depletion of biodiversity, several health problems (those leading to metabolic disorder) and ecological problems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the most acidic of the soil samples was sampling point D1 while the less acidic was the control. According to Dan et al 1 , soil pH plays a great role in determining nutrients availability and species of micro-organisms in the soil. Low mean pH values observed for the sampling points D1-4 could be as a result of decomposition of organic matter that releases carbon IV oxide which reacts with water to form carbonic acid which eventually reduces soil pH.…”
Section: Resultsmentioning
confidence: 99%
“…The result further indicates that the mean values of organic matter content in sampling points D1-4 were higher than the values at the control and this was attributed to the lower levels of biodegradable wastes at the control site than the studied abattoir soils, suggesting therefore that waste materials from the abattoir could have significantly increased the organic matter content in the soil samples D1-4 than the control. According to Dan et al 1 , soil organic matter usually acts as a store house or reservoir for most metals hence can influence their availability in the soil. Dan et al 1 reported a comparable mean organic matter content in the soils around abattoirs in Ikot-Ekpene in Akwa-Ibom State with that obtained in the soil samples of this research The mean levels of Cu in the soil samples were within WHO recommended limits.…”
Section: Organic Matter Contentmentioning
confidence: 99%
See 1 more Smart Citation